GLP-1 is an independent predictor of long-term mortality in patients with myocardial infarction complicated by cardiogenic shock – a substudy of the IABP-SHOCK II trial. (25th November 2020) - Fuernau, G; Lehrke, M; Jung, C; Kahles, F; Lebherz, C; Eitel, I; Thelemann, N; Desch, S; Werdan, K; Zeymer, U; Adams, V; Marx, N; et al.
Abstract: Background: The incretin hormone Glucagon-like-peptide 1 (GLP-1) is a major stimulus for glucose dependent insulin secretion and holds cardioprotective efficacy. This has made the GLP-1 system a preferred target for diabetes therapy. Secretion of GLP-1 happens in response to nutritional but also inflammatory stimuli. Consequently, marked elevation of circulating GLP-1 levels were found in critically ill patients featuring marked association to markers of inflammation. Purpose: Our study sought to investigate GLP-1 levels in patients with cardiogenic shock (CS) complicating myocardial infarction and a possible prognostic correlation to short- and long-term outcome. Methods: We serially assessed circulating GLP-1 levels in a prospectively planned biomarker substudy in the IABP-SHOCK II trial. Blood samples were drawn during index PCI and at day 2. The blood was centrifuged immediately, and serum was frozen at −87°C. GLP-1 was measured with a standard ELISA-kit. All-cause mortality at short- (30 days), intermediate- (1 year) and long-term (6 years) follow-up was used for outcome assessment. Results: In this study we found circulating GLP-1 to be markedly elevated in patients with myocardial infarction complicated by CS (n=172) at time of index PCI. Patients with fatal short-term outcome (n=70) exhibited higher GLP-1 levels (86 [45–130] pM) at ICU admission in comparison to patients with 30-day survival (48 [33–78] pM; p<0.001) (n=102). In repeated measures ANOVA the course of GLP-1 levels between baseline and day 2 showed a significant interaction between survivors and non-survivors (p=0.04). By univariate Cox-regression analysis GLP-1 levels >median were predictive of short- (hazard ratio [HR] 2.43; 95% confidence interval [CI] 1.50–3.94; p<0.001), intermediate- (HR 2.46; 95% CI 1.62–3.76; p<0.001) and long-term (HR 2.12; 95% CI 1.44–3.11; p<0.001) outcome. This association remained after multivariable correction (HR 2.01; 95% CI 1.37–3.07; p<0.001). In a landmark analysis we found a significant higher mortality in patients with GLP-1 levels >median from day 30 to 1 year (HR 2.56; 95% CI 1.08–6.09; p=0.03). In contrast, beyond 1 year up to 6 years no difference has been observed anymore (HR 1.02; 95% CI 0.41–2.58; p=0.96). Conclusions: Elevated plasma levels of GLP-1 are an independent predictor for impaired prognosis in patients with myocardial infarction complicated by CS at short-, intermediate and long-term follow-up. In a landmark analysis this prognostic effect is sustained up to 1 year. The functional relevance of GLP-1 in this context is currently unknown and needs further investigations. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): German Research Foundation (DFG), German Heart Research Foundation